ILMU UNTUK ILMU DAN ILMU UNTUK PEMECAHAN MASALAH - Hutajulu, Maria Magareta (Ensiklopedia of Journal, 2024)
This research aims to explore the concept of "Knowledge for Knowledge's Sake" and the role of "Knowledge for Problem-solving" and their relationship in the context of legal development and addressing complex issues. Through a conceptual analysis approach, this study dissects these concepts from epistemological, methodological, and practical perspectives. Findings indicate that the "Knowledge for Knowledge's Sake" approach emphasizes the pursuit of pure knowledge without considering its practical application, while "Knowledge for Problem-solving" leads to the application of knowledge to solve real-world problems. The implications of this research include the need for synergy between both approaches for holistic and effective knowledge development in responding to contemporary challenges. Keywords: Knowledge, Problem-solving, Epistemology, Methodology, Legal Development.